[OP.3B.05] MORNING CENTRAL BLOOD PRESSURE SURGE IS RELATED TO AGE. (September 2016) - Bednarek, A.; Jankowski, P.; Olszanecka, A.; Kloch-Badelek, M.; Windak, A.; Kawecka-Jaszcz, K.; Czarnecka, D.
Abstract : Objective: Morning surge (MS) of peripheral blood pressure (BP) is considered to be an independent risk factor for cardiovascular diseases. However, central MS has not been analyzed so far. Therefore, the aim of the study was to evaluate the variables independently associated with central MS. Design and method: Fifty never treated hypertensives (age 40.4 ± 11.5 years, 35 men) and 50 normotensive subjects (age 38.3 ± 12.0 years, 35 men) participated in the study. Applanation tonometry of the radial artery and n-point forward moving average method have been used to derive 24-h CSP (BPro, HealtStats). The sleep-through MS was calculated as the difference between the morning systolic BP (the average BP during the 2 hours after awakening) and the lowest nighttime systolic BP (the average of the lowest pressure and the 2 readings immediately preceding and after the lowest value). To assess the independent variables which correlate with MS, multiple regression analysis was used. Sex, age, BMI, smoking, 24-h mean heart rate, glucose and creatinine level, and 24-h central systolic BP were included into the model. Results: Mean central MS was 17.3 ± 7.8 mmHg in whole group, 18.6 ± 7.3 mmHg in hypertensives, and 16.1 ± 8.1 mmHg in normotensives (p = NS). There was no significant difference between women and men (16.2 ± 7.5 vs. 17.8 ± 8.0, p = 0.36) but participants at age over 40 years had lower MS compared to younger subjects (15.7 ± 7.0 vs.18.9 ± 8.3, p < 0.05). MS correlated with age (r = −0.26, p = 0.01), but not with 24-h heart rate, 24-h central systolic BP, glucose or creatinine level. Independent variables related to central MS were age (β±SE −0.30 ± 0.10, p = 0.01) and 24-h mean central systolic BP (β±SE 0.24 ± 0.10, p < 0.05). Conclusions: Central MS is related to age and mean 24-h central systolic pressure.